EFISIENSI SET PORTOFOLIO LINTAS SEKTORAL PADABURSA EFEK INDONESIA (STUDI KASUS TAHUN 2006 S.D 2015) - N. Ikawidjaja N. Ikawidjaja (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
This study is to determine an efficient portfolio in stocks sectoral wish to achieve high rates of return with minimal risikoyang. The common shares will be analyzed to establish the optimal portfolio is financials, property, and agriculture the period 2006 - 2015.Penelitian was conducted in the capital market by accessing the IDX website and got the data in the Information Center Makassar.Data capital market taken from sectoral stock indices shares the property sector, finance, and agriculture during the years 2006 to 2015. Technical analysis of the efficiency of the methods set portfolio by using the equation of elimination in order to obtain the proportion of 28.56 percent and 71.44 percent for agriculture in step 1 with the return of the portfolio amounted to 43,038,799 , - and the risk of the portfolio amounted to 1,174,755, then made the development step 2, with a 300 percent increase adjustment in order to obtain a share of 29.9% in the agriculture sector, 9.7 percent in the shares of the financial sector, and 60.4 percent of the shares in the sector property, with the return of the portfolio amounted to 43,038,799, - and the risk of a portfolio of 997 596.